Impact of 21 June 2020 Annular Solar Eclipse on Meteorological Parameters, O3 and CO at a High Mountain Site in Taiwan - Saginela Ravindra Babu; Shantanu Kumar Pani; Chang-Feng Ou-Yang; Neng-Huei Lin (Aerosol and Air Quality Research)
Abstract The annular solar eclipse observed on 21 June 2020 over Taiwan provided a rare opportunity to follow the responses of various meteorological parameters and trace gases to the solar eclipse. For the first time, the impact of the solar eclipse on solar radiation, air temperature (T), relative humidity (RH), atmospheric pressure (P), wind speed (WS), and trace gases (ozone and carbon monoxide) is delineated at the Lulin Atmospheric Background Station (LABS; 23.47°N, 120.87°E; 2,862 m MSL) in Taiwan. Over the Taiwan region, the solar eclipse began at 14:49 local time (LT; UTC+8), reached maximum obscuration at 16:13 LT, and finished at 17:24 LT. Compared to the control period (average of 13–20 June 2020), the weather parameters and trace gases show pronounced changes on the day of the eclipse (21 June 2020). A significant decrease in UV-B and solar irradiance at LABS was observed during the peak phase of the solar eclipse due to the occultation of the Sun by the Moon. On the eclipse day, the T decreased significantly (~4°C) after 17 minutes of maximum solar darkening. Due to the cloudiness and low temperatures on the day of the eclipse, 100% RH was apparent during the period of the eclipse at LABS. We also noticed a steady decline in WS just after the onset of the eclipse at LABS. Interestingly, a marked decline in ozone and carbon monoxide was seen during the eclipse day at LABS. Ozone was reduced by about 10 ppb (40%), with a delay of about 2 hours from the peak phase of the eclipse. Overall, our results show the impact of the solar eclipse on high altitude measurements for the first time, and further this work provides a useful new contribution to the literature examining solar eclipse-induced atmospheric changes.